Moderating effects of humanistic care and socioeconomic status on the relationship among pain intensity, psychological factors, and psychological function in adults with cancer pain from a province of China: A cross-sectional study - Wang, Shuyun; Wang, Xuyan; Liu, Xiaohong; Zhao, Chenxing; Duan, Jinju (Frontiers in Psychiatry, 2023)
Objective: The objective of this study is to explore whether humanistic care practiced by clinical pharmacists and socioeconomic status moderate the associations among pain intensity, psychological factors (catastrophizing and resilience), and psychological function (depression and anxiety) in cancer patients with low levels of education and income in the Shanxi province in the Northwest of China. Methods: Our sample comprised 123 adult inpatient with cancer pain. Demographic variables were obtained from the Hospital Information System of The Second Hospital of Shanxi Medical University. Pain intensity, psychological factors, and psychological functions were evaluated with four scales, and humanistic care was practiced with a part of the patients by clinical pharmacists. First, univariate analyses were conducted, followed by moderating effect models. Results: The incidence of depression and anxiety in patients with cancer pain in our sample were 48.78% and 41.46%, respectively. Low mean levels of psychological resilience (63.37, SD 21.74) were in this study. Pain intensity was significantly associated with humanistic care and anxiety. Humanistic care practiced by clinical pharmacists moderated not only the association between resilience and pain intensity but also the association between pain intensity and anxiety. Education levels moderated the relationship between pain intensity and the psychological factors of catastrophizing and resilience. Income levels moderated the association between resilience and anxiety. Conclusions. Humanistic care is essential in moderating the association among pain intensity, psychological factors, and psychological functions in Chinese cancer patients, especially those from lower-level counties and rural areas. Furthermore, socioeconomic statuses, such as education level and income, cannot easily change quickly. Still, proper humanistic care can relieve pain more effectively, reminding us that medical staff should implement effective personalized interventions to reduce patients' pain intensity.